The Crisis of Care: State, Family, and Shifting Caring Space in Contemporary Indonesia - Larastiti, Ciptaningrat; Lazuardi, Elan (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2024)
This special issue on the Crisis of Care is the result of extensive collaborative research, discussions, and interactions among contributors. In 2022, with colleagues from the University of Southampton, Atma Jaya Catholic University of Indonesia in Jakarta, and Universitas Gadjah Mada in Yogyakarta, we co-organised a conference entitled ‘Care Dynamics in Contemporary Indonesia’. Ciptaningrat Larastiti was part of a two-year research collaboration between the University of Southampton (United Kingdom) and Atma Jaya Catholic University (Jakarta), titled ‘Care Network in Later Life’. Her research focuses on care for landless older people with a state of dependency in rural Yogyakarta. Elan Lazuardi, having completed her PhD on HIV care, co-organised the conference as the representative of the Department of Anthropology, Universitas Gadjah Mada.